ESTHETICS IN REMOVABLE PARTIAL DENTURE PATIENTS VISITING UNIVERSITY DENTAL HOSPITAL - Ganapathi, Amanthi; Ganapathy, Dhanaraj; .Jeevitha, M (International Journal of Psychosocial Rehabilitation, 2025)
Removable cast partial dentures are considered a definite removable prosthesis but the location of the clasp may affect the aesthetic.A well-constructed removable partial denture can be an excellent treatment alternative for replacement thearpy .Yet, these patients deserve the best esthetic and functional results possible.The aim of this study is to evaluate the esthetic outcome of removable partial denture.In this retrospective study, the data was collected from case sheet records of 86,000 patients were postoperative removable partial denture insertion images were analyzed and score was given.The obtained data were analysed. Total of 1195 patients out of which female patients accounts for 42.19% and male patients accounts for 57.8%.Poor esthetics accounts for 26.1%,moderate esthetics accounts for 46%,and partial denture with good esthetics accounts for 27.6%.With the limitations of our study we would conclude that more number of patients receive removable partial denture with a fair amount of aesthetics. There are esthetics concerns that are still to be addressed in patients with removable partial denture.